A Study on Correlation between Serum Ascites Albumin Gradient (SAAG) and Esophageal Varices in Patients with Liver Cirrhosis in a Tertiary Level Hospital (Community Based Medical Journal, 2026)
Portal hypertension in liver cirrhosis leads to ascites and esophageal varices, and serum–ascites albumin gradient (SAAG) may reflect the portal hypertensive state. The aim of this study was to evaluate the relationship between serum–ascites albumin gradient categories and endoscopic grades of esophageal varices in patients with liver cirrhosis. This hospital-based cross-sectional observational study was conducted among indoor patients admitted to the Department of Medicine and Hepatology, Mymensingh Medical College Hospital, Mymensingh, Bangladesh, from April 2019 to March 2020. Fifty adult patients with liver cirrhosis were enrolled consecutively. Serum and ascitic fluid albumin were measured to calculate serum–ascites albumin gradient, and esophageal varices were graded by upper gastrointestinal endoscopy (Grades I–IV). The mean age was 37.05 ± 9.32 years, and 34 (68.0%) participants were male. Abdominal distension was present in 50 (100.0%), and ascites was detected in 45 (90.0%) patients consecutively. Hepatitis B virus was the leading etiology, 37 (74.0%). Serum–ascites albumin gradient values were 1.1–1.49 g/dL in 8 (16.0%), 1.50–1.99 g/dL in 29 (58.0%), and ≥2.0 g/dL in 13 (26.0%) patients consecutively. Variceal grades were Grade I 9 (18.0%), Grade II 17 (34.0%), Grade III 14 (28.0%), and Grade IV 10 (20.0%) consecutively. A progressive shift toward higher variceal grades was observed with increasing serum-ascites albumin gradient (SAAG), with the ≥2.0 g/dL group showing predominance of Grade IV varices, 9 (90.0%). Higher serum–ascites albumin gradient values clustered with more advanced esophageal variceal grades in cirrhosis, supporting its potential role as an adjunctive marker for endoscopic risk stratification.  CBMJ 2026 July: Vol. 15 No. 02 P:205-212